In vitro hepatic metabolism of the natural product quebecol. (2nd January 2023) - Bernardes, Gabriel; Krol, Ed S.
Abstract: Quebecol (2, 3, 3-tri-(3-methoxy-4-hydroxyphenyl)-1-propanol) is a polyphenolic compound, which is formed during maple syrup production from Acer spp. Quebecol bears structural similarities to the chemotherapy drug tamoxifen, which has led to synthesis of structural analogues and investigations into their pharmacological properties, however there are no reports on the hepatic metabolism of quebecol. This interest in therapeutic properties spurred us to investigate the in vitro microsomal Phase I and II metabolism of quebecol. We were unable to detect any P450 metabolites for quebecol in either human liver microsomes (HLM) or rat liver microsomes (RLM). In contrast we observed marked formation of three glucuronide metabolites in both RLM and HLM, suggesting that clearance via Phase II pathways is likely to predominate. To further understand the hepatic contribution to first-pass glucuronidation we have validated an HPLC method following FDA and EMA guidelines (selectivity, linearity, accuracy, and precision) to quantify quebecol in microsomes. In vitro enzyme kinetics were performed for quebecol glucuronidation by HLM including 8 concentrations from 5–30 µM. We determined a Michaelis-Menten constant (KM ) of 5.1 µM, intrinsic clearance (Clint, u ) of 0.038 ± 0.001 mL/min/mg, and maximum velocity (Vmax ) of 0.22 ± 0.01 µmol/min/mg.